Using simulation to estimate the uncertainty in Union Electric Company's residential customer forecast. (4th August 2014) - Weigel, Peter J.; Levary, Reuven R.
An estimation of uncertainty for Union Electric Company's residential customer forecast is made using Monte Carlo simulation. The methodology is an improvement over the deterministic simulation methodology Union Electric Company used when it filed an integrated resource plan with the Missouri Public Service Commission in 1993. Two different sensitivity analysis methodologies are applied to Union Electric Company's 1994 residential customer forecast. One methodology involves testing each discrete combination of model inputs within the uncertainty range. The other methodology involves simulating the distribution of model inputs. Neither methodology produces adequate results by itself. A combination of the two methodologies is used to efficiently determine an acceptable conclusion about forecast sensitivity.